EL AUDITOR INTERNO Y SU ROL ANTE EL FRAUDE Y LA CORRUPCIÓN - Ramón Ruffner, Jeri Gloria (2011)
This article is based on the study and analysis of internal control systems are currently operating in entities that are responsible for the country's governance and accountability of the resources to be managed. In the development will determine the quality of internal control system has been implemented in these institutions, and whether they are suitable to the requirements of modern management, accountability timely reliable, besides if measures ensure the reduction of corruption levels in the state apparatus. All this, if the internal control systems ensure compliance with its mission, vision, objectives and institutional goals for which they were created. If the assessment and analysis of the results of the investigation determined that these internal control systems are not capable of understanding the integral control, we propose a model of internal control system and the respective implementation methodology that seeks to apply a control warning or prevention at different organizational levels of public entities, especially those that citizenship considered untrusted entities.